Frat oncoproteins act at the crossroad of canonical and noncanonical Wnt-signaling pathways - van Amerongen, R; Nawijn, M C; Lambooij, J -P; Proost, N; Jonkers, J; Berns, A (Oncogene, 2010)
Wnt-signal transduction is critical for development and tissue homeostasis in a wide range of animal species and is frequently deregulated in human cancers. Members of the Frat/GBP family of glycogen synthase kinase 3β (Gsk3b)-binding oncoproteins are recognized as potent activators of the Wnt/β-catenin pathway in vertebrates. Here, we reveal a novel, Gsk3b-independent function of Frat converging on the activation of JNK and AP-1. Both these have been used as readouts for the noncanonical Frizzled/PCP pathway, which controls polarized cell movements and the establishment of tissue polarity. We find that Frat synergizes with Diversin, the mammalian homolog of the Drosophila PCP protein diego , in the activation of JNK/AP-1 signaling. Importantly, Frat mutants deficient for binding to Gsk3b retain oncogenic activity in vivo , suggesting that Wnt/β-catenin-independent events contribute to Frat-induced malignant transformation. The observed activities of Frat are reminiscent of the dual function of Dishevelled in the Wnt/β-catenin and Frizzled/PCP pathways and suggest that Frat may also function to bridge canonical and noncanonical Wnt pathways.